The effect of combinations of dried or ensiled corn and sorghum on the performance of feedlot lambs - Silva, Marina Gabriela Berchiol; Fachiolli, Daniele Floriano [UNESP]; Costa, Ciniro [UNESP]; De Lima Meirelles, Paulo Roberto [UNESP]; Factori, Marco Aurélio; Da Silva Barros, Juliana [UNESP]; Pariz, Cristiano Magalhães [UNESP]; De Lima, Vania Luzia Fournou; Garcia, Cledson Augusto (Universidade Estadual de Londrina, 2019)
The objective of this study was to evaluate the effects of combinations of dry and moist corn and sorghum grain on the carcass and cut characteristics of crossbred lambs Suffolk x Santa Inês produced in feedlots. The experimental design was a randomized block with four treatments and three replicates. Sixty uncastrated male lambs with an initial average weight of 15.5 kg were used in this experiment. Four combinations of grain were evaluated: dry sorghum milled + silage of high-moisture sorghum grain (DS: MS); dry corn milled + silage of high-moisture sorghum grain (DC:MS); dry corn milled + silage of high-moisture corn grain (DC:MC); dry sorghum milled + silage of high-moisture corn grain (DS:MC). There was no difference between treatments for carcass yield, warm and cold carcass weight and for cooling loss. The slaughtering weights of lambs fed DC:MS associations were higher (29.46 kg) than lambs fed DC: MC (24.17 kg), but both did not differ DS:MS (26.18 kg) and DS:MC (25.21 kg). There was influence of the grain associations on the yield of commercial cuts palette and shank. Combinations of corn and sorghum grain, dried and ensiled, can be used to feed lambs in confinement for meat production without affecting the quality of the carcass.
Keywords: Commercial cuts; Fat thickness; Loin eye area; Silage of high-moisture grain